Perú, país de jóvenes: Una mirada desde la antropología de la salud y la demografía - Cuadros Tairo, Raúl (2020)
The Demographic Bonus is a concept used in the demography and social sciences, it represents a unique circumstance in the population development of a country where the proportion of people of productive age exceeds that of dependent people. It means an opportunity and at the same time it can become a risk if the right conditions are not created to develop the potential of the population that is in a condition to produce. In that sense, Mental Health plays an important role in the development of a country but in this scenario it is even more so, since its participation in the design, implementation and execution of public policies as well as its articulation with other sciences is of vital importance tospecify the objectives and provide an integral development.